Effect of Silver Carp Protein Hydrolysate on Quality Properties of Frozen Dough and Bread - TIAN Jin-he; WANG Yan-jie; WU Yue; GUO Rui-rui; WANG Li-long; SUN Yu-bo (Liang you shipin ke-ji)
In order to expand the application of silver carp protein hydrolysate in frozen dough, this paper investigated the effects of silver carp protein hydrolysates on the freezable water content, water distribution and migration, microstructure, rheological properties, fermentation properties of frozen dough during frozen storage, and analyzed specific volume, textural properties and sensory score of bread. The DSC and LF-NMR results showed that the addition of silver carp protein hydrolysate inhibited the increase of freezable water content and water fluidity of dough during the frozen storage. The SEM, rheological and fermentation properties results showed that the addition of silver carp protein hydrolysate reduced the mechanical damage of gluten network structure, and increased the proportion of elastic properties and fermentation volume of dough during frozen storage. The results of specific volume and texture showed that the addition of silver carp protein hydrolysate improved the specific volume and elasticity of bread, and reduced its hardness and chewability. Silver carp protein hydrolysate also improved sensory score of bread. In conclusion, it can be seen that silver carp protein hydrolysate can effectively improve the quality of frozen dough and bread.